The Great Piratical Rumbustification - Mahy, Margaret; Blake, Quentin (London : Orion Children's Books, 2012)
In these two stories the protagonists have devilish fun with a former pirate and a band of robbers.
5.3
3-6.
3-6
Keywords: Humorous stories; Short stories; Humorous fiction; Short stories